Translation of tobacco control programs in schools: findings from a rapid review of systematic reviews of implementation and dissemination interventions. (3rd July 2014) - Wolfenden, L.; Carruthers, J.; Wyse, R.; Yoong, S.
Abstract : Issue addressed: School‐based programs targeting the prevention of tobacco use are a key strategy for reducing the overall tobacco‐related mortality and morbidity in the community. While substantial research investment has resulted in the identification of various effective tobacco prevention interventions in schools, this research investment will not result in public health benefits, unless effectively disseminated and implemented. This rapid review aimed to identify effective implementation or dissemination interventions, targeting the adoption of school‐based tobacco prevention programs. Methods: A systematic search was conducted to identify published systematic reviews that examined the effectiveness of implementation and dissemination strategies for facilitating the adoption of tobacco policies or programs in schools from 1992 to 2012. Results: The search yielded 1028 results, with one relevant systematic review being identified. The review included two controlled studies examining the implementation and dissemination of tobacco prevention programs and guidelines. The two randomised trials examined the delivery of active face‐to‐face training to implement a school‐based curriculum compared with video‐delivered or mail‐based training. Improvements in the implementation of the programs were reported for the faceto‐face training arm in both trials. Conclusions: Little rigorous evidence exists to guide the implementation and dissemination of tobacco prevention programs in schools. So what?: Few systematic reviews exist to inform the implementation of evidence‐based tobacco prevention programs in schools. In the absence of a strong evidence base, health care policymakers and practitioners may need to draw on setting‐based frameworks or parallel evidence from other settings to design strategies to facilitate the adoption of tobacco prevention initiatives. Abstract : A rapid review of the literature was conducted to identify reviews of implementation or dissemination strategies targeting the adoption of school‐based tobacco prevention programs. Only one systematic review that included two randomised controlled trials was identified. Such findings suggest the need for more reviews of implementation research in this area.